1996
DOI: 10.1530/jrf.0.1070109
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory effect of insulin-like growth factor I and epidermal growth factor on the maturation of rabbit oocytes in vitro

Abstract: The effects of different combinations of epidermal growth factor (EGF) and insulin-like growth factor I (IGF-I) on cumulus expansion and meiotic maturation were examined in rabbit oocytes. Selected rabbit follicular oocytes were matured in vitro and were classified as cumulus-oocyte complexes or denuded oocytes. They were cultured in TCM 199, and were treated with growth factors at different concentrations: EGF at 0, 1, 10, 50 and 100 ng ml-1, IGF-I at 0, 50, 100 and 200 ng ml-1 and EGF plus IGF-I at 10 + 50; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 1 publication
6
37
0
Order By: Relevance
“…Although the proportion of COCs with such slightly expanded cumulus was increased with increasing concentration of the rhIGF-I, this did not necessarily correlate with the maturation rate. The poor cumulus expansion by IGF-I is also reported in bovine [4,5] and rabbit [6] COCs. Since an "expansion" factor is produced by the oocyte [34], it is assumed that IGF-I may inhibit the production of the factor by the oocyte [4][5][6].…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Although the proportion of COCs with such slightly expanded cumulus was increased with increasing concentration of the rhIGF-I, this did not necessarily correlate with the maturation rate. The poor cumulus expansion by IGF-I is also reported in bovine [4,5] and rabbit [6] COCs. Since an "expansion" factor is produced by the oocyte [34], it is assumed that IGF-I may inhibit the production of the factor by the oocyte [4][5][6].…”
Section: Discussionmentioning
confidence: 65%
“…The poor cumulus expansion by IGF-I is also reported in bovine [4,5] and rabbit [6] COCs. Since an "expansion" factor is produced by the oocyte [34], it is assumed that IGF-I may inhibit the production of the factor by the oocyte [4][5][6]. However, this assumption may not be true under the present experimental conditions because increased concentration of rhIGF-I resulted in increased, rather than decreased, proportion of COCs with slight cumulus expansion.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The specific bindings of EGF to bovine and porcine cumulus cells have also been observed [28] and in general, it is accepted that IGF-I, EGF and insulin can activate PI 3-kinase in somatic cells [10,11]. More recently, Lorenzo et al [7] have reported that the addition of activator of PI 3-kinase, IGF-I, EGF or both factors, enhances GVBD and progresses to MII in rabbit oocytes via the gap junctions between the cumulus cells and oocytes in vitro. Additionally, FCS added to maturation medium, as in this study, contains IGF-I and stimulates cumulus cell expansion in porcine COCs [27].…”
Section: Discussionmentioning
confidence: 99%
“…After 24 hours of in vitro maturation, the degree of cumulus expansion was scored under a stereo-microscope based on the subjective scale of 0 to 3 describe by Lorenzo et al [19], in which 0 indicates no detectable response; 1 shows the minimum observable response; 2 indicates partial expansion, with more than half of the cumulus expanded; and 3 shows full expansion, where all layers of cumulus cells have expanded, including those closest to the oocyte. Then, the oocytes were mechanically denuded of the surrounding cumulus cells using repeated pipetting in 3% sodium citrate solution and were mounted on grease-free glass slides with coverslips hold in place with a mix of vaseline and paraffin wax (20:1).…”
Section: Assessment Of Oocyte Nuclear Maturation and Cumulus Cell Expmentioning
confidence: 99%